Keluarga Bersahabat Dengan Remaja (Keluarga Sahaja): Meningkatkan Keterampilan Keluarga Dalam Menyiapkan Reproduksi Sehat - Askrening; Khair Anwar, khalidatul; Yustiari; Asi, Melania (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2024)
The impact of globalization and the advancement of information technology development has an impact on rapid social changes. The social changes in question include an increase in premarital sex behavior, extramarital pregnancy carried out by adolescents, as a result of changes in the values of family and community life. Reproductive health education is a very important strategy to prevent adolescents from falling into promiscuous sexual behaviors that endanger their reproductive health.  Parents as the closest parties must have the knowledge and skills to provide reproductive health education to adolescents. However, there are still many parents in Bajoe village who still have low knowledge and skills in providing reproductive health education to their adolescents. This Community Service Program aims to build a "BERSAHAJA" family that is friendly with adolescents by equipping parents with knowledge and skills about adolescent reproductive health and ways to deal with their problems.  The method to achieve this goal is by training community leaders, health cadres and parents, especially mothers as the family side that is most talked to by adolescents about reproductive health. The main material of this training is Adolescent Reproductive Health and ways to overcome the problem, as well as how parents can become adolescent friends. The target of the program is families who have teenagers in Bajoe Village, Soropia District, Konawe Regency. The training was conducted within 2 days. The number of trainees is 30 families. The results of the activity showed that 100% of participants had good knowledge after participating in the training and 83% of participants had a good attitude related to reproductive health.